Comparative Analysis of the Performance of Linear Quadratic Regulator and State Feedback Control on DC-DC Shunt Boost Converter - I Ketut Wiryajati; Ade Safitra; Muh. Izzul Islam (Journal of Computer Science and Informatics Engineering (J-Cosine), 2024)
In recent years, DC-DC converters, particularly shunt boost types, have become essential components in power systems, especially for applications requiring efficient voltage and current regulation. Proper control of these converters is crucial for ensuring optimal performance. This study analyzes two commonly used control methods: Linear Quadratic Regulator (LQR) and State Feedback Control for shunt boost DC-DC converters. LQR is known for its ability to minimize a cost function and optimize system performance, while State Feedback Control offers a simpler yet effective approach to system state control. Through MATLAB/Simulink-based simulations, this study evaluates the performance of both methods in terms of transient response, stability, and energy efficiency. The results show that LQR offers faster and more stable responses compared to State Feedback Control. However, the complexity of LQR in implementation makes it less practical than State Feedback Control, which is easier to apply in real-time applications